High molecular weight mechanochromic spiropyran main chain copolymers via reproducible microwave-assisted Suzuki polycondensation1. Issue 19 (21st May 2015) - Metzler, Lukas; Reichenbach, Thomas; Brügner, Oliver; Komber, Hartmut; Lombeck, Florian; Müllers, Stefan; Hanselmann, Ralf; Hillebrecht, Harald; Walter, Michael; Sommer, Michael
<x xml:space="preserve">Abstract</x> Mechanochromic spiropyran main chain copolymers with high and reproducible molar mass can be made using microwave-assisted Suzuki–Miyaura polycondensation.